Farewell, Amethystine [large type] - Mosley, Walter (Mosley, Walter. Easy Rawlins mystery., 2024)
"January 1970 finds Ezekiel "Easy" Rawlins, LA's premier Black detective, at 50 years of age despite all expectations. He has a loving family, a beautiful home, and a thriving investigation agency. All is right with the world... and then Amethystine Stoller, his own personal Helen of Troy, arrives. Her ex-husband is missing. A simple enough case. But even as Easy takes his first step in the investigation he trips. He falls into the memory of things past. Little things, like loss, love, a world war, and a hunger that has eaten at him since he was a Black boy on his own on the streets of Fifth Ward, Houston, Texas. The missing ex, a young white man named Curt Fields, is found dead. Easy's only real friend in the LAPD, Melvin Suggs, has gone into hiding rather than allow his femme fatale wife to go to the gas chamber. And that's only the beginning. Easy finds himself pressed into a reckoning. All of his success cannot succor his heart. The 1970's have ushered in new expectations of men and women, Black and White, and Easy has to make a choice that will almost certainly hasten a permanent descent, one that might sunder his soul"--